PERTUMBUHAN DAN HASIL BABY CORN (ZEA MAYS) AKIBAT PENGGUNAAN NPK PHONSKA DAN PENGATURAN JARAK TANAM PADA LAHAN BERPASIR - Murdaningsih, Murdaningsih; B. Katu, Albertus; I B Hutubessy, Josina (Universitas Djuanda, 2022)
This study aims to determine the growth and yield of baby corn due to the use of NPK Phonska, to determine the growth and yield of baby corn due to the spacing of the plants and to see the interaction between the use of NPK Phonska and the regulation of plant spacing on the growth and yield of baby corn plants. The design used in this study was a factorial randomized block design (RAK) with two factors, namely P1 (350 kg/Ha) and P2 (700 kg/Ha) and the second factor was plant spacing, namely J1 (50cm X 15cm), J2 (50cm X 20cm,) and J3 (50cm X 25 cm) so that there are 6 treatment combinations, namely: P1J1, P1J2, P1J3, P2J1, P2J2, P2J3 and repeated 3 times. The variables observed in this study were plant height (cm), number of leaves (strands), leaf area (cm2), cob length, ear diameter, cob weight per plot, and cob weight per hectare. The indication of the results of this study is the combination treatment of Phonska NPK Fertilizer Application and Planting Distance there is no significant interaction on all growth variables and baby corn yields. Treatment of NPK Ponska fertilizer application 700 kg/Ha showed plant height 105 cm, number of leaves 7.41 strands, leaf area 1079.79 cm2, length of ear 12.26 cm, diameter of ear 1.70 cm, weight of cob per plot 2.54 kg and the weight of the cobs per hectare is 3.82 tons. Likewise, setting a spacing of 50x20 cm for baby corn shows a plant height of 105.86 cm, number of leaves 7.67, leaf area of ​​1310.79 cm2, length of cob 12.25 cm, diameter of cob 1.64 cm, the weight of the cobs per plot is 2.65 kg and the weight of the cobs per hectare is 3.98 tons Keywords: Baby Corn, growth, Phonska NPK, Plant Distance, yield